Defining compulsive exercise in eating disorders: acknowledging the exercise paradox and exercise obsessions - Bratland-Sanda, Solfrid (J Eat Disord, 2019)
Recently Dittmer et al. (JED 6:1–9, 2018). suggested a transdiagnostic definition and a clinical assessment for compulsive exercise in adolescents and adults with eating disorders. In this letter to the editor, we extend the transdiagnostic bridge to the DSM-5-criteria for obsessive-compulsive disorders and hence raise the issue of exercise obsession without compulsive exercise actions. We argue that, at least among persons with bulimia nervosa or binge eating disorders, a belief in the need to exercise to control food, weight and shape, does not necessarily imply that the actual exercise behaviour is excessive in nature. In our opinion, the high scores displayed on compulsive exercise screening instruments is therefore an exercise paradox. This paradox may call attention to the fact that because such obsessions can impair quality of life, they need to be addressed in the clinical evaluation and treatment. Therefore, we suggest adding “exercise obsession” as a fourth subtype of compulsive exercise.